Factors Influencing Students’ Anxiety in Speaking English: A Case Study at SMA Muhammadiyah Kalosi - Triastuti, Triastuti; Samad, Ita Sarmita; Rahmaeni, Rahmaeni (Majesty Journal, 2024)
This study investigates the factors influencing students' anxiety in speaking English at SMA Muhammadiyah Kalosi, aiming to identify specific challenges and propose practical solutions to enhance speaking performance. Employing a qualitative case study design, data were collected through semi-structured interviews, classroom observations, and document analysis of 33 high school students. The results reveal that self-perception, fear of ridicule, feelings of inability, lack of preparation, and fear of making mistakes significantly contribute to speaking anxiety. Observational data corroborate these findings, highlighting symptoms like rapid breathing and nervous laughter. Reducing anxiety includes thorough preparation, mental training, and authentic materials like English songs and films. The study emphasizes the importance of a supportive classroom environment and provides insights into effective anxiety management techniques. These findings have implications for English language teaching practices, suggesting that creating a safe space for making mistakes and incorporating engaging materials can enhance students' confidence and speaking skills. The study contributes to the broader discourse on language anxiety and offers a foundation for future research in diverse educational settings.